2001
DOI: 10.1002/ijc.1568
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of response to docetaxel by CYP3A4 mRNA expression in breast cancer tissues

Abstract: We studied the relationship between response of breast cancer to docetaxel (DOC) or cylophosphamide ؉ epirubucin (CE) treatment and CYP3A4 mRNA expression in breast tumors. CYP3A4 inactivates DOC but not E, which is a predominant effector in CE treatment. Twenty patients with locally advanced breast tumors and 18 patients with locally recurrent tumors underwent tumor biopsy before chemotherapy, and CYP3A4 mRNA expression levels in tumor tissues were assayed by real-time quantitative polymerase chain reaction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(54 citation statements)
references
References 11 publications
2
50
0
2
Order By: Relevance
“…This finding confirms previous results testing C-1311 under non-cellular conditions [16] . Namely, this compound was not metabolized by CYP3A4, which is the P450 isoenzyme with the highest abundance in the human liver and which contributes to the oxidative metabolism of more than 60% of all clinically used drugs, including antitumor agents such as cyclophosphamide [32] , ifosfamide [33] , paclitaxel [34] , tamoxifen [35,36] and doxorubicin [37] . The resistance of C-1311 to the action of other cytochrome P450 enzymes was shown previously with human recombinant enzymes from the CYP1A, CYP2C and CYP2D families [16] .…”
Section: Discussionmentioning
confidence: 99%
“…This finding confirms previous results testing C-1311 under non-cellular conditions [16] . Namely, this compound was not metabolized by CYP3A4, which is the P450 isoenzyme with the highest abundance in the human liver and which contributes to the oxidative metabolism of more than 60% of all clinically used drugs, including antitumor agents such as cyclophosphamide [32] , ifosfamide [33] , paclitaxel [34] , tamoxifen [35,36] and doxorubicin [37] . The resistance of C-1311 to the action of other cytochrome P450 enzymes was shown previously with human recombinant enzymes from the CYP1A, CYP2C and CYP2D families [16] .…”
Section: Discussionmentioning
confidence: 99%
“…The model of predictive value in terms of survival, time to treatment failure and tumour growth showed that the tumour phenotype was indeed related to the therapeutic response to 5-fluorouracil (Tanaka et al, 2004). Miyoshi et al (2002Miyoshi et al ( , 2005 showed that a low CYP3A4 expression in breast tumours, as determined at mRNA and protein level, resulted in a better response to docetaxel, which is inactivated by CYP3A4. Similarly, Dhaini et al (2003) showed that a high CYP3A expression in osteosarcoma tumours from 18 patients predicted metastasis and poor prognosis.…”
Section: Oh-docmentioning
confidence: 99%
“…Furthermore, Yamamoto et al (2005) phenotyped CYP3A4 in patients with advanced nonsmall-cell lung cancer by measuring urinary 6-beta-OHF after cortisol administration and found that an individualized dosing method, based on CYP3A4 phenotyping, decreased the pharmacokinetic variability of docetaxel when compared to body-surface area-based dosing (Yamamoto et al, 2005). In addition, CYP3A4 expression in breast tumour tissue has been shown to predict therapeutic response to docetaxel (Miyoshi et al, 2002(Miyoshi et al, , 2005. Similarly to docetaxel, irinotecan is inactivated by CYP3A4 and induction of CYP3A4 in patients receiving irinotecan results in a significant decrease in the formation of the toxic metabolite of this drug (Friedman et al, 1999;Mathijssen et al, 2002).…”
Section: P450 Pharmacogenetics C Rodriguez-antona and M Ingelman-sundmentioning
confidence: 99%
“…Its potential as a clinical diagnostic assay (Bustin & Dorudi 1998) is also being realised, and its use has been reported for the identification of micrometastases or minimal residual disease in colorectal cancer (Bustin et al 1999), neuroblastoma (Cheung & Cheung 2001), prostate cancer (Gelmini et al 2001) and leukaemia (Buonamici et al 2002). It has been used to distinguish different types of lymphoma (Bijwaard et al 2001), for the analysis of cellular immune responses in the peripheral blood (Hempel et al 2002), the detection of bacterial (Goerke et al 2001) and viral (Greijer et al 2002) RNA in clinical samples and for monitoring the response of human cancer to drugs (Miyoshi et al 2002). Other clinically relevant applications include its use for the detection of gene amplification in breast cancer (Bieche et al 1999), for the analysis of tissue-specific gene expression and for cytokine mRNA profiling (Stordeur et al 2002).…”
Section: Introductionmentioning
confidence: 99%